Multicomponent Reactions and Ultrasound: A Synergistic Approach for the Synthesis of Bioactive Heterocycles - Dandia, Anshu; Singh, Ruby; Bhaskaran, Sumit (Current Green Chemistry, 2014)
During past decades, significant advancement in the field of ultrasound assisted processes revealed that this method is broadly applicable to a variety of research fields allied to organic synthesis. Emblematically, employing this technique as key step, a great number of multicomponent reactions have been developed for the creation of an assortment of heterocyclic compounds. In this review, we attempt to give an overview about the use of multicomponent reaction under ultrasound irradiation for synthesis of various heterocyclic compounds.
Keywords: Bioactive heterocycles